2023
DOI: 10.3390/jcs7040170
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Characterization of Lithomargic Clay Deposits along the Coastal Belt of Udupi Region of South India

Abstract: Lithomargic clay is generally found below the lateritic soil along the coastal belt of Karnataka. It is rich in silt content and dispersive in nature. This type of soil is liable to erosion and landslides. The lithomargic clay is largely found in the western coast of South India. At present, coastal belt of Udupi district is witnessing a lot of developments in terms of industry, infrastructures, and other activities. Lithomargic clay is a type of problematic soil, which needs a thorough study to make it suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The investigation also revealed the existence of iron compounds, including siderite, goethite and fayalite. Oxygen, aluminum, silicon, potassium and iron comprised most of the elements found, indicating the presence of the compounds found via XRD analysis [2]. A correlation study conducted by Bhagyashree et al [3] on lateritic soil overlying lithomargic clay layer showed that the liquid limit decreases with quartz, magnetite and hematite, whereas the plastic limit increases with corundum and anatase, remains constant with quartz and decreases with magnetite and hematite.…”
Section: Introductionmentioning
confidence: 90%
“…The investigation also revealed the existence of iron compounds, including siderite, goethite and fayalite. Oxygen, aluminum, silicon, potassium and iron comprised most of the elements found, indicating the presence of the compounds found via XRD analysis [2]. A correlation study conducted by Bhagyashree et al [3] on lateritic soil overlying lithomargic clay layer showed that the liquid limit decreases with quartz, magnetite and hematite, whereas the plastic limit increases with corundum and anatase, remains constant with quartz and decreases with magnetite and hematite.…”
Section: Introductionmentioning
confidence: 90%
“…It also has an amorphous blend of Al2Si2O5(OH)4 [3]. The investigation into lithomargic clay along the Udupi region's coastal belt revealed abundant minerals, including quartz, feldspar (such as orthoclase), muscovite, kaolinite, dickite, gibbsite, halloysite and illite in substantial proportions [4]. This distinctive residual soil, known as lithomargic clay, displays a pinkish and whitish coloration and is predominantly composed of illite and kaolinite.…”
Section: Introductionmentioning
confidence: 99%